Psychology of music - Seashore, Carl E. (Carl Emil) (Dover Publications, 1967)
28 chapters: The musical mind; the musical medium; the science of music; a musical ornament, the bibrato; pitch: frequency; loudness: intensity; duration: time; timbre: wave form.